A double-blind, placebo-controlled, single ascending-dose study of remyelinating antibody rHIgM22 in people with multiple sclerosis. Issue 4 (November 2017) - Eisen, Andrew; Greenberg, Benjamin M; Bowen, James D; Arnold, Douglas L; Caggiano, Anthony O
Objective: The objective of this paper is to assess, in individuals with clinically stable multiple sclerosis (MS), the safety, tolerability, pharmacokinetics (PK) and exploratory pharmacodynamics of the monoclonal recombinant human antibody IgM22 (rHIgM22). Methods: Seventy-two adults with stable MS were enrolled in a double-blind, randomized, placebo-controlled, single ascending-dose, Phase 1 trial examining rHIgM22 from 0.025 to 2.0 mg/kg. Assessments included MRI, MR spectroscopy, plasma PK, and changes in clinical status, laboratory values and adverse events for three months. The final cohort had additional clinical, ophthalmologic, CSF collection and exploratory biomarker evaluations. Participants were monitored for six months. Results: rHIgM22 was well tolerated with no clinically significant safety signals. Noncompartmental PK modeling demonstrated linear dose-proportionality both of Cmax and AUC0–Last . The steady-state apparent volume of distribution of approximately 58 ml/kg suggested primarily vascular compartmentalization. CSF:plasma rHIgM22 concentration increased from 0.003% on Day 2 for both 1.0 and 2.0 mg/kg to 0.056% and 0.586% for 1.0 and 2.0 mg/kg, respectively, on Day 29. No statistically significant treatment-related changes were observed in exploratory pharmacodynamic outcome measures included for the 21 participants of the extension cohort. Conclusions: Single doses of rHIgM22 were well tolerated and exhibited linear PK, and antibody was detected in the CSF.